Design, synthesis and anticancer activity of novel hybrid compounds between benzofuran and N-aryl piperazine. Issue 15 (1st August 2016) - Mao, Ze-Wei; Zheng, Xi; Lin, Yu-Ping; Hu, Chun-Yan; Wang, Xiu-Li; Wan, Chun-Ping; Rao, Gao-Xiong
Graphical abstract: A series of novel hybrid compounds between benzofuran and N -aryl piperazine have been designed and prepared. These derivatives were evaluated for their in vitro anti-tumor activity against a panel of human tumor cell lines by MTT assay. The results demonstrated that amide derivatives were more bioactive than sulfonamide compounds in general, and that chloro or trifluoromethyl substituent was vital for modulating cytotoxic activity. In particular, compound13 was found to be the most potent compound against 4 strains human tumor cell lines, and exhibited cytotoxic activity selectively against Hela (0.03 μM). Abstract: A series of novel hybrid compounds between benzofuran and N -aryl piperazine have been designed and prepared. These derivatives were evaluated for their in vitro anti-tumor activity against a panel of human tumor cell lines by MTT assay. The results demonstrated that amide derivatives were more bioactive than sulfonamide compounds in general, and that chloro or trifluoromethyl substituent was vital for modulating cytotoxic activity. In particular, compound13 was found to be the most potent compound against 4 strains human tumor cell lines, and exhibited cytotoxic activity selectively against Hela (0.03 μM).